Effect of precise health management combined with physical rehabilitation on bone biomarkers in senile osteoporosis patients - Litao Chen; Xiaojing Yan; Yongjian Liu; Yongbin Pei; Jin Zhou; Lei Zhang; Zhixing Du (Scientific Reports)
Abstract This study delves into the impact of precise health management coupled with physical rehabilitation on bone biomarkers in elderly patients with osteoporosis. Two hundred and forty individuals diagnosed with senile osteoporosis were randomly assigned to either the observation group (precision health management group, n = 120) or the control group (routine health management group, n = 120). Patients in the control group received standard health care, while those in the observation group received personalized health care along with physical therapy. Pain levels (assessed by VAS score), understanding of osteoporosis, confidence in managing osteoporosis, bone density, and biochemical markers of bone metabolism were compared between the groups at 6, 12, 18, and 24 months before and after the intervention. Following the intervention, the observation group exhibited significantly reduced VAS values and PTH levels at 6, 12, 18, and 24 months compared to the control group (P < 0.05). Additionally, scores on the Osteoporosis Knowledge Scale, Osteoporosis Self-Efficacy Scale, bone mineral density (BMD), ALP levels, and calcium levels were significantly higher in the observation group compared to the control group (P < 0.05). The integration of precise health monitoring with tailored physical therapy shows substantial efficacy in reducing pain among elderly individuals suffering from osteoporosis. Moreover, it empowers them in managing their health effectively, while also contributing to increased BMD and improved bone biomarker levels. This holistic approach merits recommendation for clinical implementation and warrants further investigation through rigorous study.